2017
DOI: 10.1002/ijc.30714
|View full text |Cite
|
Sign up to set email alerts
|

The proprotein convertase furin in tumour progression

Abstract: Proprotein convertases are proteases that have been implicated in the activation of a wide variety of proteins. These proteins are generally synthesised as precursor proteins and require limited proteolysis for conversion into their mature bioactive counterparts. Many of these proteins, including metalloproteases, growth factors and their receptors or adhesion molecules, have been shown to facilitate tumour formation and progression. Hence, this review will focus on the proprotein convertase furin and its role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
117
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 124 publications
(226 reference statements)
2
117
1
2
Order By: Relevance
“…Although it is also known that furin promotes many cancer-related processes including cell proliferation, migration and invasion [2,27], we did not find an association with total cancer incidence. However, we report in the present study for the first time that increased plasma furin levels in a middleaged cohort are associated with elevated cancer mortality during long-term follow-up.…”
Section: Discussioncontrasting
confidence: 93%
“…Although it is also known that furin promotes many cancer-related processes including cell proliferation, migration and invasion [2,27], we did not find an association with total cancer incidence. However, we report in the present study for the first time that increased plasma furin levels in a middleaged cohort are associated with elevated cancer mortality during long-term follow-up.…”
Section: Discussioncontrasting
confidence: 93%
“…This discovery was consistent with our finding that FURIN was a negative indicator for CC. Furthermore, it was reported that FURIN could predict survival in ovarian cancer 31 and might be seemed as a prognostic marker and therapeutic target for cancer 32‐34 . These studies might provide further evidence for our findings that the five genes were associated with poor prognosis.…”
Section: Discussionsupporting
confidence: 79%
“…The proprotein convertase furin not only is essential for activation of certain viruses such as HPV (Richards et al., ; Schiller et al., ) but also promotes cancer development and metastasis (Jaaks & Bernasconi, ). HPV‐induced cancers mostly occur in the cervix and oropharynx.…”
Section: Discussionmentioning
confidence: 99%